Market study about indian sea logistics and analysis of sea solutions between the countries of India and Portugal - Lyyappan, Kalyanasundaram (2018)
This dissertation highlights the market research and internatonal trade of goods of India. It highlights the major import export goods traded by this country. India is an emerging country in this field and the statistics prove that international trade is flourishing and is expected to reach the peak in the coming years. Many Indian major ports are upgrading to handle this cargo traffic and deal with the trade relations. This dissertation mainly covers the import – export data relations of India with Portugal. The major goods exchanged between both the countries is explained. This also covers India’s major shipping companies which cover parts of Europe. Different sea routes between India and Portugal are analyzed and an effective sea solution is provided. Different sources have been used for the formation of this dissertation such as statistical data from sources such as Government, research papers and K Line company’s information. Data in international trade for the previous years is available and a collective information is presented in the form of graphs. As the trade in India is increasing, it becomes a good opportunity for K Line to operate a dedicated line between India and Portugal by following a transhipment route. Although Kline performed already an Asian-Europe line, with the following current transhipment ports of Rotterdam, London gateway, Singapore and Colombo. Regarding the market study of Indian sea logistics, trade between India and almost major European countries is increasing and the forecasts predicts that it will reach the maximum in the following years. Considering the possibility of K-line decided to operate between both countries, few suggestions in perspective of this view is proposed.